Ratio legis minimum percentage of share ownership of the limited company in the perspective of justice (Research, Society and Development, 2021)
This study aims to determine and analyze the ratio legis to determine the minimum percentage of 10% minority shareholding in Law Number 40 of 2007 concerning Limited Company. The methodology used in this research is normative legal research with a statute approach and a conceptual approach. The results showed that the ratio legis for determining the minimum percentage of minority share ownership of 10% in Law Number 40 of 2007 concerning Limited Company consists of four things, namely the condition of the Indonesian economy when Law Number 40 of 2007 was made, also influenced the determination the minimum percentage number for minority shareholding, so that in Indonesia the number 10% is determined, the 10% percentage number is not the majority number, the 10% number is a reasonable percentage number for shareholders who have paid up capital to be considered as minority shareholders, and the 10% number is determined. carried out by considering the value of the rupiah that has been deposited by the shareholders as paid up capital.